Perceptions of World English Varieties by Chinese EFL Students: Effects of Average Ethnic Faces and Speaker Gender - Martín Tévar, Jesús (International Journal of English Studies, 2020)
The objectives of this study are to elicit perceptions that Chinese users of English have towards a selection of world English varieties; to determine the effects of speaker gender and visual primes (ethnic faces) on perceptions; and also to reveal how these two factors interact with each other. In the present experiment, 278 respondents were exposed to eight world English varieties. Each accent sample had a female and a male voice version. Chinese students of English were exposed to these recordings, with the presence and absence of average ethnic faces as visual stimuli during the experiment, and requested to complete a questionnaire to reflect on their impressions by means of Likert scales. The results showed a preference for inner circle monolingual standards, and a rejection of outer circle Englishes (for the circles of English classification, see Kachru, 2006). Results also showed a positive perception of respondents towards their own Chinese accent. Ethnic faces visual prime and speaker gender factors, as well as their interaction, also proved to have significant influences on the results. Respondents rated accents significantly more positively when accompanied by ethnic faces.